The trouble of gender sin in post-Yugoslav film – in the name of the father - Bogojević, Maja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
Post-Yugoslav film art is, similarly to Yugoslav cinema, exemplary of masculine cultural domination, approaching socio-national themes in a highly gendered mode and reflecting a return to patriarchy, more brutal than that during the existence of Yugoslavia. A new generation of cinéasts explores, with a backlash mixture of contempt and compassion, the themes of violence, displaying a new assault on female emancipation, which seemed to be in line with the socio-political context of rising nationalist movements that led to the bloody events of the Yugoslav war in 1991. The female character is re-located to a place traditionally assigned to women not as the subject of narrative or discourse, but as the object of love and/or hatred by a masculine subject. The films chosen to be analysed here are full-length auteur feature films – Virgina, Grbavica, Djeca, Bure baruta, with a specific focus on the work by Danis Tanović – are not representative of post-Yugoslav cinema, but as rare exceptions demonstrate that, contrary to the dominant post-Yugoslav public opinion, both the Yugoslav wars and post-war traumatic realities remain cinematically unexplored.